Red Hat OpenShift container platform on IBM Z and LinuxONE - Parziale, Lydia; Krishnakumar, Rakesh; Kulkarni, Shrirang Ambaji; Liyong, Li; Patil, Anilkumar; Young, Richard (IBM Redbooks, 2024)
Whether you need to run mission-critical workloads, handle massive data volumes or support high-demand applications, Red Hat OpenShift Container Platform on IBM® Z or IBM LinuxONE can give you the tools you need to build, deploy and manage your applications. Red Hat OpenShift Container Platform provides enterprise-level support and additional features for large-scale container deployments. It includes advanced security and compliance features, as well as management tools for monitoring and scaling containerized applications. With advanced security features and flexible deployment options, Red Hat OpenShift Container Platform on IBM Z or IBM LinuxONE provides scalability, performance, reliability and security. This IBM Redpaper publication provides a basic understanding of Red Hat OpenShift Container Platform on IBM Z and LinuxONE, discusses architectural considerations for implementation as well as resource considerations, basic deployment examples and some best practices to move forwards in your own implementations. It has been written for IT architects and IT specialists.